Spatial and Temporal Distribution of Odorant-Evoked Activity in the Piriform Cortex - Rennaker, Robert L. (Society for Neuroscience, 2007)
Despite a remarkably precise spatial representation of odorant stimuli in the early stages of olfactory processing, the projections to the olfactory (piriform) cortex are more diffuse and show characteristics of a combinatorial array, with extensive overlap of afferent inputs and widespread intracortical association connections. Furthermore, although there is increasing evidence for the importance of temporal structure in olfactory bulb odorant-evoked output, little is known about how this temporal patterning is translated within cortical neural ensembles. The present study used multichannel electrode arrays and paired single-unit recordings in rat anterior piriform cortex to test several predictions regarding ensemble coding in this system. The results indicate that odorants evoke activity in a spatially scattered ensemble of anterior piriform cortex neurons, and the ensemble activity includes a rich temporal structure. The most pronounced discrimination between different odorants by cortical ensembles occurs during the first inhalation of a 2 s stimulus. The distributed spatial and temporal structure of cortical activity is present at both global and local scales, with neighboring single units contributing to coding of different odorants and active at different phases of the respiratory cycle. Finally, cross-correlogram analyses suggest that cortical unit activity reflects not only afferent input from the olfactory bulb but also intrinsic activity within the intracortical association fiber system. These results provide direct evidence for predictions stemming from anatomical- and theoretical-based models of piriform cortex.